Offering Effective Approaches to Implementation of Electronic Customer Relationship Management by the University of Applied Science and Technology (Case Study: the University of Applied Science and Technology, Unit 20, Tehran) - Ehsan Babaei; Ehram Safari; Mohammadkazem Sayadi (مدیریت مهندسی و رایانش نرم)
Universities and institutions which plan to use electronic customer relation management system (e-CRM) first need to first measure the effective factors affecting the system’s implementation so that they'll be able to provide a transparent system in order to satisfy the students and help them manage their daily activities. This article explores the effects of implementing electronic customer relationship management from the students’ viewpoint in the under-researched university. This study is an applied research regarding its purpose, and a descriptive survey research in terms of methodology. The statistical population of the research includes students studying at the University of Applied Science and Technology, unit 20. The data has been collected through researcher-designed questionnaires. The structural equation modeling was used in order to perform data analysis and hypothesis testing. Results indicate that factors such as commitment to customers, privacy protection, customers’ trust, convenience, quality electronic service, students' satisfaction and loyalty are influential in the implementation of electronic customer relationship management system. The proper implementation of e-CRM results in an increased loyalty and the satisfaction of students with the university services and programs.